VLF -MT Survey around Nakadake crater at Aso Volcano. (January 2016) - Harja, A; Srigutomo, W; Tanaka, Y; Kagiyama, T; Sutarno, D
Abstract: Shallow resistivity structure around Nakadake craters has been revealed by extensive VLF- MT survey from August to October 2006. This structure comprises a varied resistivity value at the upper and bottom layer of the western flank of craters; a conductive upper layer at the fourth Crater; and a resistive upper layer at southern part of craters. The conductive value of second layer at a line in the western flank and southern part of craters at several ten meter depth, interpreted as water saturated, and high resistivity at second line of western flank of craters as sheet of lava and at fourth crater is interpreted as lava rock. At western flank of craters, we found the resistivity value and the depth of second layer decrease in depth with decreasing of distance to craters line.